Narrative Time Structure in Biography: "my story" novel by Sheikh Mohammed bin Rashid as a model - Alkharji, Najeya Ali; Al-Hammadi, Aisha Mohammed (Al-Adab Journal, 2022)
This study intends to reveal (the structure of narrative time in the autobiography my story book by Sheikh Mohammed bin Rashid as a model) by analyzing the elements that forming the structure of time in the text. The study started with endeavor to answer a problematic question which answer determines the importance of this research, and its objective: To what extent does the biography of Sheikh Mohammed bin Rashid expose the ability to deal with narrative studies? The study proceeded in two intersecting lines, where the text resembled the point of intersection between them: the first is to study the formal structure of the text by analyzing the structural elements, and the second is to reveal the contents presented by the book. At this point, the goal of this study is determined, which is to clarify the presence of time through what is presented in the content of the book (My Story) by Sheikh Mohammed bin Rashid. The study used many Arabic sources and translated references, prefixed by the book (My Story). A Dictionary of Narratives by Gerald Pons, and a book of Storytelling by Gerald Gent. The link between form and content necessitated the use of the technical-analytical approach, which is based on monitoring the time elements, classifying them, and finally subjecting them to analysis. To determine the features of the temporal structure in the text. The research consisted of four main pivots of: the nature of time - the Time System - the rhythm of time - Time frequency. It was evident that our analysis of the Structure of Narrative time in the book My Story started from the linguistic origin of the word (time), the idiomatic conceptualization of the word, and finally the functional role of the term in building any narrative text by describing time as one of the narrative elements that make up the construction of any narrative story.